Phase diagram of an Ising model with competitive interactions on a Husimi tree and its disordered counterpart - Ostilli, Massimo; Mukhamedov, Farrukh; Mendes, Jose Fernando Ferreira (Elsevier Science BV, 2008)
We consider an Ising competitive model defined over a triangular Husimi tree where loops, responsible for an explicit frustration,are even allowed. We first analyze the phase diagram of the model with fixed couplings in which a “gas of noninteracting dimers (or spin liquid) — ferro or antiferromagnetic ordered state” zero temperature transition is recognized in the frustrated regions. Then we introduce the disorder for studying the spin glass version of the model: the triangular ±J model. We find out that, for any finite value of the averaged couplings, the model exhibits always a finite temperature phase transition even in the frustrated regions, where the transition turns out to be a glassy transition. The analysis of the random model is done by applying a recently proposed method which allows us to derive the critical surface of a random model through a mapping with a corresponding nonrandom model.